Cerebellar liponeurocytoma: clinico-epidemiological, pathological, radiological, genetic, therapeutic and evolutionary characteristics—a review of the literature - Ahmed Jribi; Fatma Dhouib; Wicem Siala; Nejla Fourati; Jamel Daoud (Egyptian Journal of Neurosurgery, 2024)
Abstract Cerebellar liponeurocytoma is a rare benign tumor of the central nervous system affecting adults and mainly the posterior fossa. Its positive diagnosis remains difficult due to its rarity and the presence of several differential diagnoses including medulloblastoma. The oncogenetic mechanism, the therapeutic modalities and results are still currently under study. Very few cases have been published in the literature. The aim of this review is to report, through the available data, all its various clinico-epidemiological, pathological, radiological, genetic, therapeutic and evolutionary features. In fact, this tumor is associated with a slow-growing character, appears in young adulthood with slight female predominance and is often manifested by intracranial hypertension symptoms. It is pathologically characterized by a focal component of lipomatous differentiation and a low proliferation index. It is usually presented in imaging by a well-limited mass with signal attenuation for fatty tissue and heterogeneous contrast. No mutation has been identified yet. The gold standard treatment of this tumor is maximal complete resection. The evolutionary profile is marked by frequent local recurrence. Radiotherapy could be discussed in case of recurrence, incomplete surgery, inoperable cases and cases with high proliferation index, and there is to date no proof of benefit for systemic treatment. Due to the numerous similarities of this entity with medulloblastoma, it should be always evoked face to any suspicion of medulloblastoma in adults in order to avoid a wrong overtreatment.